Energy Efficiency Optimization of Multi-user Switching and Scheduling in EH-SBS System - Cao, Yu; Xiao, Kun (IEEE Information Technology, Networking, Electronic and Automation Control Conference (Online), 2023)
Due to the dynamic influence of user flow and environment, the small and dense cellular networks powered by renewable energy can lead to the load imbalance between cells and the difference in energy harvesting level. In order to make effective use of system resources, the energy harvesting small base station (EH-SBS) system adopts a strategy combining user scheduling and adaptive adjustment of cell handover parameters. Under the premise of ensuring the long-term service quality of users and system resource constraints, we establish an optimization problem to maximize the energy efficiency of the system. Firstly, the lists of switching users and candidate base stations are updated based on the system state. Then, the particle swarm optimization (PSO) algorithm is used to optimize the cell individual offset (CIO) based on the optimal user association target of proportional fairness. The simulation results show that this strategy has good performance in the outage ratio of service quality of small base station users and system energy efficiency.